Effect of warming and acidification on polar lipid fatty acid composition in juvenile European sea bass (Dicentrarchus labrax) - Romain Gonzalvez; Mickaël Péron; Margaux Mathieu-Resuge; Fabienne Le Grand; Mishal Cohen-Rengifo; Sophie Collet; Philippe Soudant; Marie Vagner (Marine Environmental Research, 2026)

The first record of Achilidae (Hemiptera: Fulgoromorpha) in Miocene Dominican amber revealed by synchrotron X-ray tomography - Mathieu Boderau; Ancheng Peng; Chen Feng; Romain Garrouste; Corentin Jouault; André Nel (Palaeoworld, 2026)

Experimental determination of uranium isotope fractionations during early diagenesis of green rust - Loren Tessier; Morten B. Andersen; Franck Poitrasson; Armel Descamps-Mandine; Camille Duquenoy; Ludovic Menjot; Pauline Méjean; Jérôme Chmeleff; Carole Causserand; Mathieu Leisen; Romain Guilbaud (Geochimica et Cosmochimica Acta, 2026)

Influence of garden composition and gardening practices on the biodiversity of residential garden: a systematic map - Muriel Deparis; Quentin Dutertre; Mathieu Lachaise; Romain Sordello; Emmanuelle Baudry (Urban Ecosystems, 2026)

A digital twin integrating multi-objective optimization to support fryer operators in managing potato crisps production - Manon Perrignon; Mathieu Emily; Mélanie Munch; Paul Debuire; Romain Jeantet; Thomas Croguennec (Journal of Food Engineering, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Effect of consumption temperature of whole milk on in vitro gastric digestion using a biomimetic digestion simulator - Jiajun Feng; Jeehyun Lee; Vincent Mathieu; Yann Le Gouar; Romain Jeantet; Didier Dupont; Steven Le Feunteun (Food Research International, 2026)

Indirect assessment of autonomic nervous system balance for prediction of hemorrhage: A preclinical study in a porcine model - Mathieu Magnin; Amandine Chapelle; Stéphane Junot; Bernard Allaouchiche; Timothée Schuhler; Romain Lac; Valentin Bondoux; Guillaume L. Hoareau; Mark Kim; Tatiana Victoni; Céline Pouzot-Nevoret (Research in Veterinary Science, 2025)

Mapping benthic biodiversity indicators of coral reefs using spatial interpolation - Léo Broudic; Mathieu Pinault; Romain Claud; Touria Bajjouk; Tévamie Rungassamy; Natacha Nikolic; Estelle Crochelet; Camille Mazé; Benjamin Bergerot (Coral Reefs, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Machine learning for predicting industrial performance: Example of the dry matter content of emmental-type cheese - Manon Perrignon; Mathieu Emily; Mélanie Munch; Romain Jeantet; Thomas Croguennec (International Dairy Journal, 2025)

Effects of repeated cryostimulation exposures on sleep and wellness in healthy young adults - Coralie Arc-Chagnaud; Olivier Dupuy; Manuela Garcia; Laurent Bosquet; Romain Bouzigon; Robin Pla; Arc-Chagnaud Coralie; Bosquet Laurent; Bretonneau Quentin; Delpech Nathalie; Dugué Benoit; Dupuy Olivier; et al. (Cryobiology, 2024)

The multi-objective data-driven approach: A route to drive performance optimization in the food industry - Manon Perrignon; Thomas Croguennec; Romain Jeantet; Mathieu Emily (Trends in Food Science & Technology, 2024)

Study of humic-like substances of dissolved organic matter using size exclusion chromatography and chemometrics - Sylvain Faixo; Romain Capdeville; Sofiane Mazeghrane; Mathieu Haddad; Gilberte Gaval; Etienne Paul; Florence Benoit-Marquié; Jean-Christophe Garrigues (Journal of Environmental Management, 2024)

Primary cell cultures from the single-chromosome ant Myrmecia croslandi - Alain Debec; Romain Peronnet; Michael Lang; Mathieu Molet (Chromosome Research, 2024)

The second genus of pond treaders (Heteroptera: Mesoveliidae) from mid-Cretaceous amber of Myanmar - Mathieu Boderau; Valérie Ngô-Muller; Romain Garrouste; André Nel (Annales de Paléontologie, 2024)

Plant-TFClass: a structural classification for plant transcription factors - Romain Blanc-Mathieu; Renaud Dumas; Laura Turchi; Jérémy Lucas; François Parcy (Trends in Plant Science, 2024)

Pulmonary Histoplasmosis in People Living with Human Immunodeficiency Virus in French Guiana: Clinical Epidemiology, Medical Imaging and Prognostic - Morgane Bourne-Watrin; Antoine Adenis; Gary Doppelt; Magaly Zappa; Loïc Epelboin; Mathieu Nacher; Jeanne Bigot; Kinan Drak Alsibai; Romain Blaizot; Denis Blanchet; Magalie Demar; Geneviève Guillot; et al. (Mycopathologia, 2023)
Background Histoplasmosis is mainly described as a disseminated disease in people living with HIV (PLHIV). Compared to historical descriptions in immunocompetent individuals, knowledge is lacking on the detailed clinical and radiological findings and outcomes of pulmonary histoplasmosis (PH). Overlooked or misdiagnosed with other AIDS-defining condition, prognostic of PLHIV may be at risk because of inappropriate care. Methods A retrospective multicentric study was conducted in PLHIV from French Guiana between January 1988 and October 2019. Proven PH were documented through mycological direct examination, culture, or histology. Patients with concomitant respiratory infections were excluded. Results Among 65 patients, sex ratio M:F was 2.4 with a median age of 39 years [IQR 25–75%: 34–44]. Median CD4 count was 24 cells/mm 3 [11–71], with histoplasmosis as the AIDS-defining condition in 88% and concomitant AIDS-defining conditions in 29%. Clinical findings were fever (89%), cough (58%), dyspnea (35%), expectoration (14%), and hemoptysis (5%). Sixty-one X-rays and 24 CT-scans were performed. On X-rays, an interstitial lung disease was mainly found (77%). On CT-scans, a nodular pattern was predominant (83%): mostly miliary disease (63%), but also excavated nodules (35%). Consolidations were present in 46%, associated with miliary disease in 21%. Thoracic lymphadenopathies were found in 58%, mainly hilar and symmetric (33%). Despite antifungal treatment, case-fatality rate at one month was 22%. Conclusion When faced with an interstitial lung disease on X-rays or a miliary pattern on CT-scans in advanced PLHIV, physicians in endemic areas, apart from tuberculosis or pneumocystosis, should include histoplasmosis as part of their differential diagnoses.

The DeepFaune initiative: a collaborative effort towards the automatic identification of European fauna in camera trap images - Noa Rigoudy; Gaspard Dussert; Abdelbaki Benyoub; Aurélien Besnard; Carole Birck; Jérome Boyer; Yoann Bollet; Yoann Bunz; Gérard Caussimont; Elias Chetouane; Jules Chiffard Carriburu; Pierre Cornette; et al. (European Journal of Wildlife Research, 2023)

A multi-isotopic study reveals the palaeoecology of a sebecid from the Paleocene of Bolivia - Yohan Pochat-Cottilloux; Jeremy E. Martin; Mathieu G. Faure-Brac; Stéphane Jouve; Christian de Muizon; Jorge Cubo; Christophe Lécuyer; François Fourel; Romain Amiot (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Persistent organochlorine pesticides in periprostatic adipose tissue from men with prostate cancer: Ethno-geographic variations, association with disease aggressiveness - Jean-Philippe Antignac; Sandy Figiel; Michèle Pinault; Pascal Blanchet; Franck Bruyère; Romain Mathieu; Souhil Lebdai; Georges Fournier; Jerome Rigaud; Karine Mahéo; Philippe Marchand; Ingrid Guiffard; et al. (Environmental Research, 2023)

The ID NOW COVID-19, a high-speed high-performance assay - Eric Farfour; M. Asso-Bonnet; M. Vasse; Emilie Catherinot; Colas Tcherakian; Antoine Magnan; Simon Chauveau; Sylvie Colin de Verdière; Hélène Salvatore; Antoine Roux; Benjamin Zuber; Charles Cerf; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Inversion breakpoints and the evolution of supergenes - Romain Villoutreix; Diego Ayala; Mathieu Joron; Zachariah Gompert; Jeffrey L. Feder; Patrik Nosil (Molecular Ecology, 2021)
The coexistence of discrete morphs that differ in multiple traits is common within natural populations of many taxa. Such morphs are often associated with chromosomal inversions, presumably because the recombination suppressing effects of inversions help maintain alternate adaptive combinations of alleles across the multiple loci affecting these traits. However, inversions can also harbour selected mutations at their breakpoints, leading to their rise in frequency in addition to (or independent from) their role in recombination suppression. In this review, we first describe the different ways that breakpoints can create mutations. We then critically examine the evidence for the breakpoint‐mutation and recombination suppression hypotheses for explaining the existence of discrete morphs associated with chromosomal inversions. We find that the evidence that inversions are favoured due to recombination suppression is often indirect. The evidence that breakpoints harbour mutations that are adaptive is also largely indirect, with the characterization of inversion breakpoints at the sequence level being incomplete in most systems. Direct tests of the role of suppressed recombination and breakpoint mutations in inversion evolution are thus needed. Finally, we emphasize how the two hypotheses of recombination suppression and breakpoint mutation can act in conjunction, with implications for understanding the emergence of supergenes and their evolutionary dynamics. We conclude by discussing how breakpoint characterization could improve our understanding of complex, discrete phenotypic forms in nature.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Manipulation of worker size diversity does not affect colony fitness under natural conditions in the ant Temnothorax nylanderi - Romain Honorio; Claudie Doums; Mathieu Molet (Behavioral Ecology and Sociobiology, 2020)

Multiple glacial refugia and contemporary dispersal shape the genetic structure of an endemic amphibian from the Pyrenees - Federica Lucati; Manon Poignet; Alexandre Miró; Audrey Trochet; Fabien Aubret; Laurent Barthe; Romain Bertrand; Teresa Buchaca; Olivier Calvez; Jenny Caner; Elodie Darnet; Mathieu Denoël; et al. (Molecular Ecology, 2020)
Historical factors (colonization scenarios, demographic oscillations) and contemporary processes (population connectivity, current population size) largely contribute to shaping species’ present‐day genetic diversity and structure. In this study, we use a combination of mitochondrial and nuclear DNA markers to understand the role of Quaternary climatic oscillations and present‐day gene flow dynamics in determining the genetic diversity and structure of the newt Calotriton asper (Al. Dugès, 1852), endemic to the Pyrenees. Mitochondrial DNA did not show a clear phylogeographic pattern and presented low levels of variation. In contrast, microsatellites revealed five major genetic lineages with admixture patterns at their boundaries. Approximate Bayesian computation analyses and linear models indicated that the five lineages likely underwent separate evolutionary histories and can be tracked back to distinct glacial refugia. Lineage differentiation started around the Last Glacial Maximum at three focal areas (western, central and eastern Pyrenees) and extended through the end of the Last Glacial Period in the central Pyrenees, where it led to the formation of two more lineages. Our data revealed no evidence of recent dispersal between lineages, whereas borders likely represent zones of secondary contact following expansion from multiple refugia. Finally, we did not find genetic evidence of sex‐biased dispersal. This work highlights the importance of integrating past evolutionary processes and present‐day gene flow and dispersal dynamics, together with multilocus approaches, to gain insights into what shaped the current genetic attributes of amphibians living in montane habitats.

Effects of plant traits and their divergence on runoff and sediment retention in herbaceous vegetation - Léa Kervroëdan; Romain Armand; Mathieu Saunier; Michel-Pierre Faucon (Plant and Soil, 2019)

Dendritic sodium spikes endow neurons with inverse firing rate response to correlated synaptic activity - Tomasz Górski; Romain Veltz; Mathieu Galtier; Hélissande Fragnaud; Jennifer S. Goldman; Bartosz Teleńczuk; Alain Destexhe (Journal of Computational Neuroscience, 2018)

Constitutive calcium entry and cancer: updated views and insights - Olivier Mignen; Bruno Constantin; Marie Potier-Cartereau; Aubin Penna; Mathieu Gautier; Maxime Guéguinou; Yves Renaudineau; Kenji F. Shoji; Romain Félix; Elsa Bayet; Paul Buscaglia; Marjolaine Debant; et al. (European Biophysics Journal, 2017)

Slow feature analysis with spiking neurons and its application to audio stimuli - Guillaume Bellec; Mathieu Galtier; Romain Brette; Pierre Yger (Journal of Computational Neuroscience, 2016)

Phytoextraction from mine spoils: insights from New Caledonia - Guillaume Losfeld; Romain Mathieu; Laurent L’Huillier; Bruno Fogliani; Tanguy Jaffré; Claude Grison (Environmental Science and Pollution Research, 2015)